Comparison of Extraction Techniques for Wide Screening of 230 Pesticides in Water - Caterina Cacciatori; Jackie Myers; Giulio Mariani; Hung Vu; Bernd Manfred Gawlik; Vincent Pettigrove (Separations)
In this study, weekly grab samples extracted by solid-phase extraction (SPE) and stir bar sorptive extraction (SBSE) were compared for the analysis of 230 pesticides in surface waters. Samples were collected from three different locations around Melbourne, Australia. Analysis was performed using Gas Chromatography Quadrupole Time of Flight High Resolution Mass Spectrometry (GC-QToF-HRMS). The two extraction techniques were compared, among others, for their limits of detection, recovery, extraction, and quantification efficiency of pesticides, as well as spatial and temporal differences in detected compounds. The target compounds screened were pesticides belonging mainly to the categories of fungicides, insecticides, and herbicides. Although SBSE extracted more pesticides at two out of three sites, SPE extracted total concentrations up to four times higher than SBSE over all sampling sites. The log KOW of detected pesticides only partially explained the differences in detection, with SBSE performing better in the absorption of hydrophobic compounds. In addition, matrix effects, in particular turbidity, appeared to hinder extraction of contaminants, especially for SBSE. Spatially, SBSE detected 10 pesticides more than SPE at two locations, while the opposite was true at the third location, where turbidity was higher. The types of pesticides detected varied slightly between techniques and locations. The study highlights the complementarity of SBSE and SPE for monitoring pesticides in natural environments. SBSE is an easy-to-use technique and allows for extraction of a higher number of pesticides at trace level, but it might not be the preferred option for highly turbid waters. SPE requires more tedious and complex sample processing but allows for a more accurate quantification of a broader range of pesticides.